Culture Caleidoscoop’s inaugural issue: Mapping socially engaged practice in the cultural sector - Carter, Danielle; Cruickshanks, Lorna (Culture Caleidoscoop, 2022)
An introduction to the inaugural issue of Culture Caleidoscoop – ‘Working with and for people: Mapping socially engaged practice in the cultural sector’. In this issue we wanted to explore the main focus of Culture Caleidoscoop: socially engaged practice in the arts, cultural, and heritage sectors, revealing what this kind of practice looks like in different organisations and to people working in different roles and around the globe. In this editorial we reflect upon the response we had to our first call for contributions and give an indication of what you can expect from the first issue. We indicate some of the themes that have emerged and the questions the pieces we already have pose. We also look ahead, as we look forward to continuing to build on these perspectives.